Robotics in Language Learning: A Systematic Review - Psara, Eftihia; Parmaxi, Antigoni; Athanasiou, Androulla (My University, 2022)
In this paper, scientific literature on the use of robotics in language learning from 2000 to 2020 is being reviewed. The paper is guided by specific questions regarding: a) the type(s) of robots that have been used in language learning, b) the benefits and challenges of the use of robotics in language classrooms, c) the skills that have been targeted with the use of robotics, d) future research directions recommended in the literature, e) the evaluation methods of learning and knowledge of students, f) the languages that have been explored through Robotic Assisted Language Learning (RALL), g) the educational levels in which RALL has been investigated and h) the geographical distribution in countries in which RALL research has been conducted. A systematic online search on bibliographic databases was conducted and 63 articles were selected and included in the study. Amongst the major benefits concluded in the review are the positive effects on motivation, as well as the decrease of embarrassment and discomfort. Challenges include the distraction caused in classrooms when robots are used, technical issues and the individual differences of learners. Based on the results of the review, future directions and recommendations are also pointed out for researchers interested in RALL.
Keywords: Robot-assisted-language-learning; RALL; Systematic review; Language learning